The Relationship Between Language and Emotion:: Insights of Psycholinguistics - Sinaga, Jonathan Halomoan; Damanik, Bernieke Anggita Ristia (Cahaya Ilmu Bangsa Institute, 2025)
This study investigates the complex interrelationship between language and emotion, looking at how vocabulary and linguistic patterns influence how people express and comprehend their emotions. Based on multidisciplinary research from the fields of psychology, linguistics, and neuroscience, the study emphasises how language functions as a medium for emotional communication, impacting interpersonal relationships and personal identity. The concept of emotional intelligence and its relationship to language skills are discussed in the study, along with cultural differences in emotional lexicons. The results of qualitative and quantitative assessments show that language is essential for controlling and interpreting emotions in addition to reflecting emotional states. This piece adds to the larger conversation of how cognitive functions and emotional experiences interact, arguing that language is an essential for emotions and the formation of social bonds.